Patterned Immobilization of Antibodies within Roll-to-Roll Hot Embossed Polymeric Microfluidic Channels - Feyssa, Belachew (Public Library of Science, 2013)
This paper describes a method for the patterned immobilization of capture antibodies into a microfluidic platform fabricated by roll-to-roll (R2R) hot embossing on poly (methyl methacrylate) (PMMA). Covalent attachment of antibodies was achieved by two sequential inkjet printing steps. First, a polyethyleneimine (PEI) layer was deposited onto oxygen plasma activated PMMA foil and further cross-linked with glutaraldehyde (GA) to provide an amine-reactive aldehyde surface (PEI-GA). This step was followed by a second deposition of antibody by overprinting on the PEI-GA patterned PMMA foil. The PEI polymer ink was first formulated to ensure stable drop formation in inkjet printing and the printed films were characterized using atomic force microscopy (AFM) and X-ray photoelectron spectroscopy (XPS). Anti-CRP antibody was patterned on PMMA foil by the developed method and bonded permanently with R2R hot embossed PMMA microchannels by solvent bonding lamination. The functionality of the immobilized antibody inside the microfluidic channel was evaluated by fluorescence-based sandwich immunoassay for detection of C-reactive protein (CRP). The antibody-antigen assay exhibited a good level of linearity over the range of 10 ng/ml to 500 ng/ml (R(2) = 0.991) with a calculated detection limit of 5.2 ng/ml. The developed patterning method is straightforward, rapid and provides a versatile approach for creating multiple protein patterns in a single microfluidic channel for multiplexed immunoassays.